47.4k views
1 vote
-12.2z - 13.4z=-179.2.

idk how to do this ​

User Allenru
by
5.8k points

1 Answer

6 votes

Let's solve your equation step-by-step.

12.2

z

13.4

z

=

179.2

Step 1: Simplify both sides of the equation.

12.2

z

13.4

z

=

179.2

12.2

z

+

13.4

z

=

179.2

(

12.2

z

+

13.4

z

)

=

179.2

(Combine Like Terms)

25.6

z

=

179.2

25.6

z

=

179.2

Step 2: Divide both sides by -25.6.

25.6

z

25.6

=

179.2

25.6

z

=

7

Answer:

z

=

7

User Mnesarco
by
5.5k points